Blind Benchmark Exercise for Spent Nuclear Fuel Decay Heat. (2nd September 2022) - Jansson, Peter; Bengtsson, Martin; Bäckström, Ulrika; Álvarez-Velarde, Francisco; Čalič, Dušan; Caruso, Stefano; Dagan, Ron; Fiorito, Luca; Giot, Lydie; Govers, Kevin; Hernandez Solis, Augusto; Hannstein, Volker; et al.
Abstract: The decay heat rate of five spent nuclear fuel assemblies of the pressurized water reactor type were measured by calorimetry at the interim storage for spent nuclear fuel in Sweden. Calculations of the decay heat rate of the five assemblies were performed by 20 organizations using different codes and nuclear data libraries resulting in 31 results for each assembly, spanning most of the current state-of-the-art practice. The calculations were based on a selected subset of information, such as reactor operating history and fuel assembly properties. The relative difference between the measured and average calculated decay heat rate ranged from 0.6% to 3.3% for the five assemblies. The standard deviation of these relative differences ranged from 1.9% to 2.4%.